EFEKTIVITAS PENDEKATAN PROBLEM POSING PADA MATERI BARISAN DAN DERET ARITMATIKA DI SMK - Sapinah Sapinah; Zubaidah Zubaidah; Bistari Bistari (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractThis research aimed to know the effectiveness of applying problem posing approach in learning arithmetic sequence and series topic at class XI SMK. The research method used was pre-experimental method with one-shot case study design. The aspect to determine the effectiveness of the problem posing approach were teacher’s class management, student’s activity, student’s outcomes and student’s respond. Data collection tools used are student’s outcomes test which contains 4 essay, student’s respond questionnaire sheet and the observation sheet for teacher’s class management and student’s activity. The result of the descriptive analysis carried out were teacher’s class management categorized good (3,11), student’s activity categorized active (65,59%), student’s completeness not fulfilled classically (only 23 students or 66,97% of students can fulfill the standard completeness) and student’s respond categorized good (64%). Because there was one aspect that not fulfilled, so the applying of problem posing approach in learning arithmetic sequence and series at class XI SMK was not effective. Keywords: Arithmetic Sequence and Series, Effectiveness, Problem Posing Approach.